Hypothetical Learning Trajectory (HLT) Based on STEM-Ethnomathematics Puru Timbu to Improve Elementary School Students' Mathematical Communication Skills - Sukma Mawaddah; Ahyansyah Ahyansyah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to develop and test the effectiveness of the Hypothetical Learning Trajectory (HLT) based on STEM-Ethnomathematics Puru Timbu in improving the mathematical communication skills of elementary school students. The background of this study is based on students' low mathematical communication skills as indicated by difficulties in explaining the solution process, using mathematical symbols consistently, and communicating mathematical ideas orally and in writing. The study uses a Design Research approach that includes three stages, namely preliminary design, teaching experiment, and retrospective analysis. The subjects of the study were 20 fifth-grade elementary school students in Bima Regency who were selected by purposive sampling. Data were collected through mathematical communication skills tests, observations, interviews, documentation, and student worksheets. The developed HLT integrates the STEM approach with Puru Timbu ethnomathematics through cultural observation activities, traditional and modern measurement experiments, making miniature bamboo models, compiling contextual questions, as well as presentations and group discussions. The results of the study indicate that the developed HLT has contextual, collaborative, and student-centered characteristics and is able to facilitate the development of mathematical communication through representation, argumentation, and reflection. Quantitatively, there was an increase in the average score of students' mathematical communication skills from 62.15 in the pretest to 81.40 in the posttest. The results of the paired t-test showed a significance value of p = 0.000 < 0.05, which indicated a significant increase after the implementation of HLT. These findings indicate that HLT based on STEM-Ethnomathematics Puru Timbu is effective in improving the mathematical communication skills of elementary school students and can be an alternative design for contextual, meaningful, and local wisdom-based mathematics learning.